Suprapatelární hřebování zlomenin bérce – hodnocení klinických a rentgenologických výsledků - Křivohlávek, M; Šrám, J; Pazour, J; Kloub, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY The locked nailing of diaphyseal fractures of the tibia currently represents a method of choice for treating the closed diaphyseal fractures, some of the tibial metaphyseal fractures and open tibial diaphyseal fractures classified as grade I and II according to Gustilo-Anderson (GA) classification. The suprapatellar (SP) approach is an alternative technique of insertion of the nail in semi-extension of the lower extremity with easier reduction, namely of multiple fractures and proximal diaphyseal fractures of the tibia in particular. This study aims to evaluate the group of patients in whom the suprapatellar approach was used and who were followed up for the period of at least 12 months. MATERIAL AND METHODS The prospective study included 55 cases of osteosynthesis of diaphyseal fractures of the tibia with the surgery performed in the period from January 2013 to June 2015, of which in 53 patients (17 women and 36 men) with the mean age of 49.6± 16.7 years the ETN nail by DePuy Synthes ® was inserted through a suprapatellar approach. In 38 cases (70.1%) an isolated trauma was involved, 15 patients (29.9%) were treated for multiple injuries or polytrauma. In nine cases (17%) it was an open fracture (2times - GA grade I, 7times - GA grade II). A multiple fracture or a fracture of the proximal third was recorded in 19 cases (34.5%). The functional and radiological results of the treatment were assessed prospectively at 12 months after the surgery using the Lysholm (LS) score. RESULTS The final functional results were successfully assessed in 49 performed osteosyntheses (89.1%). The mean duration of surgery was 72.7± 19.57 min (40-140 min, median 65 min). A total of 48 (98%) fractures healed by primary intention. In five cases (10.2%) a delayed healing occurred and in one case (2 %) non-union was reported, requiring a revision surgery. In three cases (6.1%) complete implant was removed (twice by SP and once by IP approach). The mean Lysholm score was 93.4 ± 8.39 points (59-100 points, median score of 95 points). An excellent or a good result was observed in 45 patients (91.8%), a satisfactory result in three patients (6.2%), and a poor result in one patient (2%). A statistically significant correlation (p = 0.006) between the LS score values and the age of the patients was confirmed. In patients up to 60 years of age the LS score was 96.2 ± 4.51 points (89-100, median 96), at the age of more than 60 years it was 86.9 ± 11.46 (59-100, median 89). CONCLUSIONS The suprapatellar approach in treating the tibial diaphyseal fractures represents a safe alternative nail insertion technique. If an appropriate surgical technique is applied, the risks inherent in this approach are negligible. The approach allows for an easy reduction of challenging fractures of the proximal third diaphyseal fracture of the tibia and multiple fractures of the tibia and facilitates an easy check of the axial position of the extremity. The functional results of the knee joint are comparable to those achieved with the infrapatellar nailing technique. The final LS score correlates with the age of the patients. Key words:tibial fractures, suprapatellar approach, intramedullary nailing, knee pain.
Keywords: diafýzy; Humans; fraktury tibie; Radiography; lidé středního věku; Fractures, Closed; Tibial Fractures; radiografie; Female; Aged; intramedulární fixace fraktury; dospělí; Fractures, Open; senioři; lidé; Lysholm Knee Score; Bone Nails; Adult; kostní hřeby; ženské pohlaví; Male; Middle Aged; uzavřené fraktury; Lysholmovo skóre; Fracture Fixation, Intramedullary; Diaphyses; mužské pohlaví; prospektivní studie; otevřené fraktury; Prospective Studies